Pemberdayaan dan Peningkatan Kapasitas Kelompok Masyarakat Lintas Komunitas Seni Kelurahan Kebun Keling Kota Bengkulu Melalui Digital Innovative Product dan Smart Management - Mochammad Yusa; Arie Vatresia; Chairil Afandy (Jurnal SOLMA, 2021)
Kebun Keling Sub-district is an area of coast in Bengkulu. It is one of Bengkulu City's mainstay tourist destinations. In this sub-district, there is a community group which has a strong commitment to become productive people. The art community is the Lintas Komunitas Seni which is based on Kebun Keling Sub-district in Teluk Segara District, Bengkulu City. This community incorporates to musical, classical motobike, mural, and fine art. Several obstacles are faced the digitalization era of the creative industry, including the level of understanding of digital design technology, organizational management and production. The aim of this series activities is to apply science and technology through Digital Innovative Products and Smart Management. It is the initiation of economic independence for member of this art community group in Kebun Keling sub-district, Teluk Segara District. The method of implementing this activity is divided into 3 (three) main activities, such as: (1) Implementing digital drawing techniques by converting paper images into curves using graphic design softwares, (2) making and assisting in producing handicrafts from digital art conversion to become a ready-to-sell product using afdruk screen printing techniques, (3) accompanying financial management assistance and training with the cost of production method to determine the selling value, profit and loss, and asset management. The activity target is to improve the technology and management capabilities, soft and hard skills, and knowledge of the partner. The result from evaluation of series activitieswe have done by filling out a questionnaire were that the partners' knowledge and skills are increased.